Entrepreneurial intentions among medical laboratory technology students: effect of education and self-efficacy - Subhaktiyasa, Putu Gede; Sutrisna, I Gusti Putu Agus Ferry; Sumaryani, Nyoman Putri; Sunita, Ni Wayan (Journal of Education and Learning (EduLearn), 2024)
The role of entrepreneurship in addressing the issue of educated unemployment is well acknowledged, while its specific implications for health professions students remain inadequately explored. This study's main objective is to investigate entrepreneurship education's effect on entrepreneurial intention by considering entrepreneurial self-efficacy as a mediator in students majoring in medical laboratory technology. This quantitative research uses an exploratory approach involving 300 respondents determined through simple random sampling techniques and analyzed using partial least square structural equation model (PLS-SEM). The analysis revealed that entrepreneurship education directly impacts self-efficacy and entrepreneurial intention. Furthermore, entrepreneurial self-efficacy was identified to exert a positive mediating effect between these variables. However, the effect size between the relationships of the research variables is low. Nevertheless, higher education offering health majors can optimize entrepreneurship education by implementing practical learning and field experience to increase confidence and intention in entrepreneurial activities.